Implementing place-based education to enhance ecological empathy and conservation intention - Bimo Aji Nugroho; Hery Fajeriadi (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
Environmental education is often limited to cognitive understanding, creating a gap between environmental knowledge and actual conservation actions. This research is crucial due to the decrease in empathy and enthusiasm for conservation efforts among students, which stems from a learning process that is non-contextual and limited to the classroom. This research aims to test the effectiveness of the Place-Based Education (PBE) paradigm in enhancing students' ecological empathy and conservation aspirations. This pre-experimental study used a one-group pretest-posttest design with 33 participants from the Biology Education Study Programme at the University of Borneo Tarakan. The intervention was carried out through direct observation in the Mangrove and Proboscis Monkey Conservation Area in Tarakan City. The collected data were examined using paired sample t-tests, effect size calculations (Cohen's d), and standardised gain (N-gain). The research findings show a substantial increase (p < 0.001) in both variables, accompanied by a very large effect size. The increase in conservation intention (N-Gain = 0.66) was observed to exceed the increase in ecological empathy (N-Gain = 0.35). In short, PBE-based learning is capable of transforming passive information into active commitments and encouraging action-oriented behaviour. The implementation of PBE in the future can be applied as a pedagogical approach to develop sustainability traits. A long and sustained intervention process is required to deeply cultivate empathy.Abstrak Pendidikan lingkungan sering kali terbatas pada pemahaman kognitif, menciptakan kesenjangan antara pengetahuan lingkungan dan tindakan konservasi yang nyata. Penelitian ini sangat penting karena menurunnya empati dan antusiasme terhadap upaya konservasi di kalangan siswa, yang disebabkan oleh proses pembelajaran yang tidak kontekstual dan terbatas di dalam kelas. Penelitian ini bertujuan untuk menguji efektivitas paradigma Pendidikan Berbasis Tempat (PBE) dalam meningkatkan empati ekologis dan aspirasi konservasi siswa. Studi preeksperimental ini menggunakan desain pretest-posttest satu kelompok dengan 33 peserta dari Program Studi Pendidikan Biologi Universitas Borneo Tarakan. Intervensi dilakukan melalui observasi langsung di Kawasan Konservasi Mangrove dan Bekantan di kota Tarakan. Data yang dikumpulkan diperiksa menggunakan uji t sampel berpasangan, perhitungan ukuran efek (d Cohen), dan keuntungan terstandarisasi (N-gain). Temuan penelitian menunjukkan peningkatan substansial (p < 0.001) pada kedua variabel, disertai dengan ukuran efek yang sangat besar. Ditemukan bahwa peningkatan dalam niat konservasi (N-Gain = 0.66) melebihi peningkatan dalam empati ekologis (N-Gain = 0.35). Singkatnya, pembelajaran berbasis PBE mampu mengubah informasi pasif menjadi komitmen aktif dan mendorong perilaku yang berorientasi pada tindakan. Implementasi PBE di masa depan dapat diterapkan sebagai pendekatan pedagogis untuk mengembangkan sifat keberlanjutan. Un proceso de intervención largo y sostenido es necesario para cultivar profundamente la empatía.